HRI for interactive humanoid head Amir-II for visual tracking and servoing of human face. - Iqbal, Aseef; A Shafie, Amir; Khan, Md. Raisuddin; Alias, Mohd Farid; Radhi, Jamil (Computer science Journals, 2011)
In this paper, we describe the HRI (Human-Robot Interaction) system developed to operate a humanoid robot head capable of visual tracking and servoing of human face through image processing. The robotic humanoid head named Amir-II, equipped with a camera and servoing mechanism is used as the platform. The Amir-II tracks the human face within the field-of-vision (FOV) while the servoing mechanism ensures the detected human face remains at the center of its FOV. The algorithm developed in this research utilizes the capability offered by scientific computing program MATLAB along with its Image Processing Toolbox. The algorithm basically compares the locations of the face in the image plane that is detected from the static face image captured from real-time video stream. The calculated difference is then used to produce appropriate motion command for the servo mechanism to keep track of the human face moving within the range of its FOV.